The fuzzy value of patent litigation under imprecise information - Elettra Agliardi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
The vague notion of "probabilistic patents" is formalized through a model which combines real option theory and a fuzzy methodology. The imprecise estimates the patent holder possesses about her future profits, the validity and scope of the patent, the litigation costs, the court's decision etc. under a regime of imperfect inforcement of property rights are specified modelling uncertainty with fuzzy sets. Such methodology is embedded within a real option approach, where the value of a patent includes the option value of litigation. We study how the value of a patent is affected by the timing and incidence of litigation. The main results are compared with the empirical findings of previous results.
Keywords: 330